Factors determining gender pension gap in Europe: A cross national study - Petroula M. Mavrikiou; Julijana Angelovska (UTMS Journal of Economics, 2020)
The objective of this paper is to investigate the factors that determine the gender pension gap in Europe. In particular, we focus on understanding how and which risk factors create the pension gap among the two genders. To extract the risk factors that determine the gender pension in Europe, we use EU-SILC and LFS data from Eurostat. For our analysis we engage descriptive and inferential statistics and the software IBM SPSS. EU countries are clustered in two groups based on the gender pension gap. Women working part time, and gender differences in working life duration, were found to be the two most significant factors that determine the pension gap. Gender pay gap, was not found to be significant due to the paradox that some countries exhibit, high gender pay gap and low pension gap.
Keywords: J16; J31; N30; 330; gender pension gap; gender pay gap; working life patterns; gender differences